Analisis Faktor Penyebab Contract Change Order dan Pengaruhnya Terhadap Pelaksanaan Proyek Konstruksi Jalan dan Jembatan - Dinda Fardila; M. Syarif Afandy; Eti Kurniati (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The Contract Change Order problems in construction projects significantly influence the project’s success. Therefore, analysis related to the factors causing the occurrence of CCO and its effect on the implementation of construction projects is expected to be used as a reference by related parties for future project implementation. This research used quantitative and descriptive methods to find out which factors caused CCO and their effects. The study was carried out on one road acceleration project in NTB Province with the owners, consultants, and contractors who were respondents to this research. There are 14 variables in the causative factor of CCO and two variables in the influence that occurs.